AKTIVITAS ANTIMIKROBA FLAVONOID - GLIKOSIDA HASIL SINTESIS SECARA TRANSGLIKOSILASI ENZIMATIK - Yati Sudaryati Soeka; Elidar Naiola; Joko Sulistyo (BERITA BIOLOGI, 2007)
Flavonoid-glycoside was synthesized enzymatically using CGT-ase (EC.2.4.1.19) of indigenous Bacillus licheniformis in a phosphate buffer pH 6.0 at 45°C for 24 h, through transglycosylation reaction in the present of flavonoid those were extracted from rhizomes such as ginger, flngerroot, turmeric, white turmeric and white curcuma as natural acceptors, and commercial rice,cassava, corn and wheat flour as substrates.The result showed that CGT-ase of B. licheniformis transferred a glycosyl moiety in a bilayer enzymatic reaction system of n-hexanol and phosphate buffer yielding glycosides as transfer products in the present of wheat flour as substrate and white curcuma extract as its acceptor.An inhibitory effects of the synthesized flavonoid glycosides against microbial growth was furthermore examined. It was found that flavonoid-glycoside, as the transfer product, exhibited high antimicrobial activity at MIC 200 ppm on the growth of Bacillus subtilis, Escherichia coli and Saccharomyces cerevisiae, however no effect when it was assayed on Candida tropicalis, while arbutin and flavonoid-aglycon showed very low inhibitory activity on the growth of two out of four tested microbial strains.